Give fudge a chance - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2023)
The Mackinac County fair is in full swing, and the air is rich with the scent of funnel cakes and the sound of carnival rides. Allie is focused on the fudge competition--another win would really put her hotel and fudge shop on the map. But she's willing to take a little break and walk through the haunted house attraction with her friend Jenn. When they come across a body, though, it turns out not to be a prop. Soon Allie's cop boyfriend is on the scene, and the sleuthing confectioner is hunting for clues. Danger strikes too close to home when the hotel becomes the scene of a suspicious fatal accident, and Allie suspects the two deaths are connected. The case is turning into a real rollercoaster. Allie will need to hold on tight . . .